PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAPAT DI BURSA EFEK INDONESIA - NONI LISTIA SARI; HIKMAH . (JURNAL ILMIAH KOHESI, 2020)
This study aims to obtain explanative findings that are tested on the effect of: (1) Return On Assets on stock prices, (2)Current Ratio of stock prices in manufacturing companies listed on the Indonesian stock exchange in the period 2015-2018.The research design used in this study is a causal quantitative design. The research subjects were 10 companies with thehighest profit per period listed on the Indonesian stock exchange, and the variables were ROA, CR and stock prices. Datawere collected by document recording technique, and analyzed by multiple linear regression analysis. The results of thisstudy indicate that (1) Partially Return on Assets have a significant effect on stock prices (2) Partially Current Ratio has nosignificant effect on stock prices (3) Simultaneously Return on Assets and Current Ratio have a significant effect on stockprices.